A New Approach to Identifying Red Supergiant Stars in Metal-poor Galaxies: A Case Study of NGC 6822 - Zhi-wen Li; Ming Yang; Biwei Jiang; Yi Ren (The Astrophysical Journal)
A complete sample of red supergiant (RSG) stars is important for studying their properties. Identifying RSGs in extragalactic fields first requires removing the Galactic foreground dwarfs. The color–color diagram (CCD) method, specifically using r − z / z − H and J − H / H − K , has proven successful in several studies. However, in metal-poor galaxies, faint RSGs will mix into the dwarf branch in the CCD and would be removed, leading to an incomplete RSG sample. This work attempts to improve the CCD method in combination with the Gaia astrometric measurement to remove foreground contamination in order to construct a complete RSG sample in metal-poor galaxies. The empirical regions of RSGs in both CCDs are defined and modified by fitting the locations of RSGs in galaxies with a range of metallicity. The metal-poor galaxy NGC 6822 is taken as a case study for its low metallicity ([Fe/H] ≈ −1.0) and moderate distance (about 500 kpc). In the complete sample, we identify 1184 RSG, 1559 oxygen-rich AGB (O-AGBs), 1075 carbon-rich AGB (C-AGBs), and 140 extreme AGB (x-AGBs) candidates, with a contamination rate of approximately 20.5%, 9.7%, 6.8%, and 5.0%, respectively. We also present a pure sample, containing only the sources away from the dwarf branch, which includes 843 RSG, 1519 O-AGB, 1059 C-AGB, and 140 x-AGB candidates, with a contamination rate of approximately 6.5%, 8.8%, 6.1%, and 5.0%, respectively. About 600 and 450 RSG candidates are newly identified in the complete and pure samples, respectively, compared to the previous RSG sample in NGC 6822.